Labelisasi Halal, Kualitas Produk dan Harga Pengaruhnya Terhadap Keputusan Pembelian Produk-Produk UMKM Saffa Tjahya Lestari - Hani Hatimatunnisani; Ramayani Yusuf; Rini Susilowati; Mira Veranita (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
Saffa Tjahya Lestari as an SME that produces snacks made from mushrooms has been affected by the pandemic, and is currently struggling to increase consumer buying interest again. Saffa Tjahya Lestari together with other MSMEs must rise and compete, among others, by carrying out halal labeling on products, improving product quality and determining competitive prices. Knowing the effect of halal labeling, product quality and price on purchasing decisions for SMEs Saffa Tjahya Lestari products is the goal of this study. Descriptive quantitative methods were used in this study, the overall results showed that the three labeling variables, namely halal, product quality and price, had an effect on the purchasing decision process for Saffa Tjahya Lestari products. This shows that for consumers of confectionary products made from mushrooms, UKM Saffa Tjahya Lestari, halal, quality and price of food products are very important for the convenience of consuming.